Richness and abundance of epigeal macrofauna in four tropical systems of Chiapas, Mexico - Mancilla -Brindis, Rubén Francisco; Rangel Ruiz, Luis José; Falcón-Brindis, Armando; Gamboa Aguilar, Jaquelina; Valdez Leal, Juan de Dios (Instituto de Ecología, A.C., 2018)
We sampled four vegetation systems with different degree of disturbance (i. e. tropical forest, mature and young secondary forest, and a cornfield) in northern Chiapas, Mexico. The objective of this study was to determine the differences in the composition and structure of macroinvertebrate communities in litter. We estimated abundance (N), species richness (S), Shannon’s diversity (H´), Pielou’s evenness (J), and Morisita-Horn’s similarity index. Twenty samples were randomly placed in each system by using 1-m2 quadrats. Leaf litter and organic matter (humus) were collected from the quadrat to a depth of 5.0 cm, with the purpose of collecting only the epigeous macroinvertebrates. We collected 1,259 specimens from three phyla, nine classes, 26 orders, 61 families, 17 genera, and 100 morph types. The highest N and S were observed in the tropical forest, however, the highest diversity (H´) occurred in the young secondary forests. The cornfield showed the highest evenness. There was a positive relation between the systems’ conservation level and macroinvertebrate abundance, but not with species richness.